On the EU-Japan roadmap for experimental research on corium behavior. (February 2019) - Bechta, Sevostian; Ma, Weimin; Miassoedov, Alexei; Journeau, Christophe; Okamoto, Koji; Manara, Dario; Bottomley, David; Kurata, Masaki; Sehgal, Bal Raj; Stuckert, Juri; Steinbrueck, Martin; Fluhrer, Beatrix; et al.
Highlights: A review of ongoing severe accident studies on corium behavior was presented. A comparison of research priorities identified in different projects was performed. An EU-Japan roadmap on research of corium behavior was suggested for bilateral collaborations. Abstract: A joint research roadmap between Europe and Japan has been developed in severe accident field of light water reactors, focusing particularly on reactor core melt (corium) behavior. The development of this roadmap is one of the main targets of the ongoing EU project SAFEST. This paper presents information about ongoing severe accident studies in the area of corium behavior, rationales and comparison of research priorities identified in different projects and documents, expert ranking of safety issues, and finally the research areas and topics and their priorities suggested for the EU-Japan roadmap and future bilateral collaborations. These results provide useful guidelines for (i) assessment of long-term goals and proposals for experimental support needed for proper understanding, interpretation and learning lessons of the Fukushima accident; (ii) analysis of severe accident phenomena; (iii) development of accident prevention and mitigation strategies, and corresponding technical measures; (iv) study of corium samples in European and Japanese laboratories; and (v) preparation of Fukushima site decommissioning.